Cardiopulmonary exercise testing following acute pulmonary embolism: Systematic review and pooled analysis of global studies - Gabriella VanAken; Daniel Wieczorek; Drew Rubick; Ahmad Jabri; Domingo Franco‐ Palacios; Gillian Grafton; Bryan Kelly; Olusegun Osinbowale; Syed T. Ahsan; Rana Awdish; Herbert D. Aronow; Supriya Shore; et al. (Pulmonary Circulation)
Abstract Recent reports have revealed a substantial morbidity burden associated with “post‐PE syndrome” (PPES). Cardiopulmonary exercise testing (CPET) has shown promise in better characterizing these patients. In this systematic review and pooled analysis, we aim to use CPET data from PE survivors to understand PPES better. A literature search was conducted in PubMed, EMBASE, and Cochrane for studies reporting CPET results in post‐PE patients without known pulmonary hypertension published before August 1, 2023. Studies were independently reviewed by two authors. CPET findings were subcategorized into (1) exercise capacity (percent predicted pVO2 and pVO2) and (2) ventilatory efficiency (VE/VCO2 slope and VD/VT). We identified 14 studies (n = 804), 9 prospective observational studies, 4 prospective case‐control studies, and 1 randomized trial. Pooled analysis demonstrated a weighted mean percent predicted pVO2 of 76.09 ± 20.21% (n = 184), with no difference between patients tested <6 months (n = 76, 81.69±26.06%) compared to ≥6 months post‐acute PE (n = 88, 82.55 ± 21.47%; p = 0.817). No difference was seen in pVO2 in those tested <6 months (n = 76, 1.67 ± 0.51 L/min) compared to ≥6 months post‐acute PE occurrence (n = 144, 1.75 ± 0.57 L/min; p = 0.306). The weighted mean VE/VCO2 slope was 32.72 ± 6.02 (n = 244), with a significant difference noted between those tested <6 months (n = 91, 36.52 ± 6.64) compared to ≥6 months post‐acute PE (n = 191, 31.99 ± 5.7; p < 0.001). In conclusion, this study, which was limited by small sample sizes and few multicenter studies, found no significant difference in exercise capacity between individuals tested <6 months versus ≥6 months after acute PE. However, ventilatory efficiency was significantly improved in patients undergoing CPET ≥ 6 months compared to those <6 months from the index PE.